Crack growth modeling and simulation of a peridynamic fatigue model based on numerical and analytical solution approaches. (August 2021) - Bang, D.J.; Ince, A.; Oterkus, E.; Oterkus, S.
Highlights: The peridynamic fatigue model is solved by numerical and analytical approaches. Experimental data of 2024-T3 aluminum is used for the model validation. The numerical approach has shortcomings in accurate crack growth predictions. The analytical approach offers good prediction accuracy for various load cases. Abstract: Fatigue crack growth assessment of 2024-T3 aluminum alloy is carried out on the basis of a recently developed peridynamic fatigue model. The governing remaining-life equation of the peridynamic fatigue model has been solved by two different approaches i.e. numerical and analytical approaches to perform fatigue-crack growth simulations for 2024-T3 aluminum specimen with a pre-existing crack. Remaining-life parameters of the numerical and analytical solution approaches are determined by calibrating with the experimental crack growth data. Fatigue crack growth predictions, and associated material deformation of the specimen under various loading conditions are simulated by the two approaches. Predicted results show that the numerical approach has shortcomings in accurate predictions of crack growth rates for the application of different loading conditions, while the analytical approach can be applied for a wide range of loading conditions with good prediction accuracy and stable simulations of the material deformation with a growing crack. Furthermore, it is found that the computational time of the analytical approach is considerably shorter in comparison with the numerical approach.